Maritime transportation accidents: A bibliometric analysis - Vicky Zampeta; Gregory Chondrokoukis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The article aims to highlight the concept of risk management in maritime transportation accidents in the specialized literature on the Web of Sciences database through existing materials. Design/methodology/ approach: The keyword study identifies several keywords as they have been set in this study and as they appear in the Web of Science database. Using VOSviewer our main concern is to identify and highlight the most essential and questioned words associated with the "maritime accidents" and "other issues related with maritime accidents" concept. We extracted 456 articles, underlined 259 keywords with the similar meaning to the keywords we have selected in the previous stage. Findings: We found that the maritime transportation accidents (MTA) topic has limited expansion in the literature. The gaps are considerably big leaving space for further research. The analysis of the keywords proves an interconnection between the MTA, the risk models, safety, management organization and more. Research limitations/implementations: Although there has been an increased interest in this field especially among countries with the shipping sector highly developed (maritime universities in China, London Poland, etc.), we have noticed that the related studies are still at the beginning, especially if we consider the accounting side of this subject. Originality value: The present article can only be the beginning of a set of studies in MTA, given that the issue has an increasing interest in academia. For future research, we can consider using a larger sample, more keywords, and additional databases.
Keywords: M40; D81; G32; 330; Shipping risk management; bibliometric mapping; VOSviewer; maritime transportation accidents